Surrounding rock pressure calculation based on time functions and stress release rate determination of deep soft rock tunnel: taking Zhonghe Tunnel as an example - Ding, Xiao; Deng, Xianghui; Zhang, Xuan; Wang, Rui (Frontiers in Earth Science, 2023)
On the basis of the Zhonghe tunnel project of the An-Lan Expressway, the objective is to determine the appropriate method of calculating steel arch load and the stress release rate during numerical simulation. First of all, based on the monitoring results of 6 similar tunnel sections, the surrounding rock exerted pressure on the steel arch, using time functions, the rock pressure time-history curve could be fitted, two formulas for calculating stable rock pressure in deep tunnels were compared, and the calculation model suitable for the Zhonghe tunnel project was constructed. Then, a simulation of the Zhonghe tunnel was performed using Flac3D, and stress release was simulated using the Mana method. Via comparing the surrounding rock characteristic curves and the initial support characteristic curves under different stress release rates, the impact pattern of stress release rate on support load was summarized, and appropriate excavation stress release rate was determined based on the stable rock pressure value calculating. There was a finding in the results that the Zhonghe tunnel rock pressure calculation model could better depict the change in rock pressure over time based on the empirical formula and Weibull time function. A prediction of steel arch load of Zhonghe Tunnel could be made using this method, and the stress release rate of numerically simulated rock excavation was determined to be 0.5. This study thus provides a basis for future internal force analysis and support parameter design of support systems.